Oxygen supply and oxygen-dependent gene expression in differentiating embryonic stem cells. - Gassmann, M (1996)
Blastocyst-derived pluripotent mouse embryonic stem cells can differentiate in vitro to form so-called embryoid bodies (EBs), which recapitulate several aspects of murine embryogenesis. We used this in vitro model to study oxygen supply and consumption as well as the response to reduced oxygenation during the earliest stages of development. EBs were found to grow equally well when cultured at 20% (normoxia) or 1% (hypoxia) oxygen during the first 5 days of differentiation. Microelectrode measurements of pericellular oxygen tension within 13- to 14-day-old EBs (diameter 510-890 micron) done at 20% oxygen revealed efficient oxygenation of the EBs' core region. Confocal laser scanning microscopy analysis of EBs incubated with fluorescent dyes that specifically stain living cells confirmed that the cells within an EB were viable. To determine the EBs' capability to sense low oxygen tension and to specifically respond to low ambient oxygen by modulating gene expression we quantified aldolase A and vascular endothelial growth factor (VEGF) mRNAs, since expression of these genes is upregulated by hypoxia in a variety of cells. Compared with the normoxic controls, we found increased aldolase A and VEGF mRNA levels after exposing 8- to 9-day-old EBs to 1% oxygen. We propose that EBs represent a powerful tool to study oxygen-regulated gene expression during the early steps of embryogenesis, where the preimplantation conceptus resides in a fluid environment with low oxygen tension until implantation and vascularization allow efficient oxygenation.